2023
DOI: 10.1126/sciimmunol.adf8161
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to lung-migrating helminth protects against murine SARS-CoV-2 infection through macrophage-dependent T cell activation

Abstract: Helminth endemic regions report lower COVID-19 morbidity and mortality. Here, we show that lung remodeling from a prior infection with a lung-migrating helminth, Nippostrongylus brasiliensis , enhances viral clearance and survival of human-ACE2 transgenic mice challenged with SARS-CoV-2 (SCV2). This protection is associated with a lymphocytic infiltrate, including increased accumulation of pulmonary SCV2-specific CD8 + T cells, and anti-CD8 antibody depletion abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 108 publications
2
6
0
Order By: Relevance
“…On the other hand, alveolar macrophages, the tissue resident macrophages of the lung, did not contribute significantly to the M2 macrophage pool, despite the increased frequencies of ILC2 and Th2 in the lungs of susceptible mice, as their frequencies gradually decreased at day 4 and 8 p.i. These results are consistent with previous studies that have shown that monocyte-derived macrophages replace alveolar macrophages and acquire an alternatively activated macrophage transcriptional profile induced by tissue-migrating nematodes, which persists long after worm elimination 51 . Hence, in susceptible mice, the increased Ascaris L3 count found in the lungs during primary infection seems to directly translates into an elevated number of recently recruited monocyte-derived M2 macrophages that present dim expression of F4/80 52 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, alveolar macrophages, the tissue resident macrophages of the lung, did not contribute significantly to the M2 macrophage pool, despite the increased frequencies of ILC2 and Th2 in the lungs of susceptible mice, as their frequencies gradually decreased at day 4 and 8 p.i. These results are consistent with previous studies that have shown that monocyte-derived macrophages replace alveolar macrophages and acquire an alternatively activated macrophage transcriptional profile induced by tissue-migrating nematodes, which persists long after worm elimination 51 . Hence, in susceptible mice, the increased Ascaris L3 count found in the lungs during primary infection seems to directly translates into an elevated number of recently recruited monocyte-derived M2 macrophages that present dim expression of F4/80 52 .…”
Section: Discussionsupporting
confidence: 93%
“…Long-term tissue remodeling can result from even transitory helminth infection. In the lung, a chronically altered lung tissue environment includes a persistent M2 macrophage phenotype, which not only has anti-helminth properties, as discussed earlier, but also protects against infection with SARS-Cov-2, even as late as 28 d after N. brasiliensis inoculation (Oyesola et al, 2023) . However, the remodeling can also take an aberrant course, as observed in the IL-17–dependent emphysema that is severe by 30 d after N. brasiliensis infection ( Chen et al, 2018 ; Marsland et al, 2008 ), even though the parasite resides in the lung for only 2–3 d. Interestingly, RELMα production by B cells 1–2 d after infection controls IL-17 elevations, delaying development of emphysematous pathology ( Chen et al, 2018 ).…”
Section: Aftermath: Repair and Return To Homeostasismentioning
confidence: 85%
“…IV BCG is not a unique non-specific stimulus for host protection against experimental SCV2. In addition to prior M. tuberculosis infection (37,43,44), recent findings indicate that intranasally administered PRR ligands can also trigger host resistance in the same murine models (48)(49)(50) as can prior infection with a lungtransiting helminth (51). While seemingly distinct stimuli, it is possible that they all act by triggering the production of anti-viral effectors by pulmonary myeloid or epithelial cells.…”
Section: Discussion and Translational Implicationsmentioning
confidence: 99%